The Effect of Co-Creation Value on Umrah Pilgrims’ Loyalty: The Moderating Role of Digital Engagement - Muhammad Bayu Kreshna; Fatchur Rohman; Radityo Putro Handrito (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines the effect of co-creation value on Umrah pilgrims’ loyalty and investigates the moderating role of digital engagement in the relationship. Grounded in Service-Dominant Logic (SDL), this research emphasizes the importance of customer participation in value creation within service interactions. A quantitative approach was employed using a survey of Umrah pilgrims who had experience using Umrah travel services in Jakarta. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that co-creation value has a positive and significant effect on pilgrims’ loyalty, indicating that active customer participation in service processes enhances long-term relationships with the travel agency. However, digital engagement was not found to significantly moderate the relationship between co-creation value and loyalty. These findings suggest that loyalty in Umrah travel services is primarily driven by direct service experiences and value co-creation rather than by digital interaction alone. This study contributes to the Service-Dominant Logic literature by extending the application of co-creation value in the context of religious service marketing and provides practical insights for Umrah travel agencies seeking to strengthen customer loyalty.